On Josep Ferrater Mora’s integrationism: the possibility of oscillating - Sales i Coderch, Jordi (Journal of Catalan Intellectual History, 2014)
This paper sets Ferrater Mora’s integrationist philosophy against the larger background of the opposition between dogmatism and scepticism in the theory of knowledge. Oscillating between these two positions, which is key in Ferrater Mora’s definition of integrationism, can help us unlock the unresolved tension caused by their dichotomy and also poses its own difficult questions in the process. key words Josep Ferrater Mora, integrationism, theory of knowledge.